Analysis of organic and conventional lowland rice (Oryza sativa L) cultivation in supporting environmentally friendly agriculture in the District Banyan tree, Deli Serdang Regency - Zulfansyah, Ichpan; O Tambunan, Jubelando; Nur Asima Sidabutar, Melisa; Jusnita Samosir, Herna; Samosir, Alexander (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
The application of organic farming to paddy rice farming is one of the interesting topics in an effort to reduce environmental pollution caused by the use of chemical fertilizers and pesticides. This study aims to determine the level of production and analyze the environmental impact of the soil from the application of organic and conventional farming in Beringin subdistrict, Deli Serdang district. The results showed that 1) There was a significant difference between the production of dry harvested grain (GKP) in organic paddy rice and the production of dry harvested grain (GKP) in conventional paddy rice. 2) The level of soil fertility in organic and conventional rice farming has low criteria